Tratamento cirúrgico dos carcinomas basocelular e espinocelular: experiência dos Serviços de Cirurgia Plástica do Hospital Ipiranga Surgical treatment of basal and squamous cell carcinomas: experience of the Plastic Surgery Services of Hospital Ipiranga - Júlia Broetto; José Octávio Gonçalves de Freitas; Aymar Edison Sperli; Suk Won Soh; Carlos Augusto Richter; Ricardo Antonio de Toni (Revista Brasileira de Cirurgia Plástica)
INTRODUÇÃO: Os tumores de pele malignos não-melanoma são o tipo de câncer de maior incidência e prevalência no Brasil. Dentre eles, o carcinoma basocelular (CBC) é o mais comum, correspondendo entre 70% e 75% dos casos. O carcinoma epidermoide (CEC) responde por 20% dos casos. Este trabalho tem por objetivo analisar os casos de câncer de pele não-melanoma operados, entre os anos de 2005 e 2010, no Serviço de Cirurgia Plástica do Hospital Ipiranga. MÉTODO: Foi realizada análise de prontuários de pacientes submetidos a exérese de carcinoma de pele não-melanoma em centro cirúrgico, avaliados quanto a idade, sexo, profissão, raça, localização anatômica, fatores de risco, número de lesões e subtipo histológico. RESULTADOS: Foram analisados 145 pacientes, dos quais 15,9% apresentavam lesões múltiplas, totalizando 168 tumores. Houve predomínio de CBC, correspondendo a 87,6% dos casos, seguido de CEC, com 26,2%. Os CBCs sólidos ou nodulares predominaram, com 44,1%, e os CECs Broders I representaram 42,1% dos CECs. Dos pacientes, 80,7% possuíam lesão em face e 12,4%, em membros superiores. A média de idade dos pacientes foi de 69,5 anos, sendo 59,4% do sexo feminino. A raça branca foi mais frequente e o tabagismo foi o principal fator de risco, presente em 79,3% dos casos. CONCLUSÕES: Observou-se predomínio de CBC e do sexo feminino nos pacientes estudados, demonstrando a tendência atual desse tumor. O número significativo de pacientes com lesões múltiplas ressalta a importância do exame periódico dessa população. A alta prevalência de tabagismo entre os pacientes não pode deixar de ser observada. BACKGROUND: A higher incidence and prevalence of non-melanoma skin cancers has been reported in Brazil. Among them, basal cell carcinoma (BCC) is the most common, accounting for 70%-75% of all cases. Squamous cell carcinoma (SCC) constitutes 20% of non-melanoma skin cancers. The aim of this study was to examine the patients who underwent surgery for the treatment of non-melanoma skin cancer between 2005 and 2010 at the Plastic Surgery Service of Hospital Ipiranga. METHODS: The medical records of the patients who were treated for non-melanoma skin cancer at the surgical center were reviewed and classified according to age, gender, occupation, race, anatomical location, risk factors, number of lesions, and histological subtype. RESULTS: A total of 145 patients were evaluated; 15.9% exhibited multiple lesions, which resulted in a total of 168 tumors. BCC was most commonly detected (87.6% of the tumors), whereas 26.2% of tumors were SCC. Solid or nodular BCC comprised 44.1% of all skin cancers, whereas Broders I SCC accounted for 42.1% of SCC cases. The lesions were present on the face in 80.7% of the patients and on the upper limbs in 12.4%. The average patient age was 69.5 years, and 59.4% of the patients were female. The tumors were more commonly observed in Caucasians, and smoking was the major risk factor recorded in 79.3% of cases. CONCLUSIONS: The patients with cancer in this study tended to have BCC and/or were predominantly female - observations that reflect the current tendency of this tumor. The presence of a significant number of patients with multiple lesions emphasizes the importance of undergoing a periodic examination. Moreover, high smoking rates were observed among these patients.